Pip Bartlett's guide to unicorn training - Pearce, Jackson; Stiefvater, Maggie, 1981- (Pearce, Jackson. Pip Bartlett series, 2017)
Pip Bartlett has a way with the magical creatures at her Aunt Emma's clinic, but an extremely timid unicorn named Regent Maximus is testing even her abilities--particularly since it is Pip's assignment to get Regent ready for the Triple Trident show for magical animals where, to make matters worse, somebody is trying to win by sabotaging the other contestants.